RETRACTED: Control of Bidirectional DC-DC Converter for Micro-Energy Grid’s DC Feeders' Power Flow Application - Muhammad Hammad Saeed; Wang Fangzong; Basheer Ahmed Kalwar (International Journal of Renewable Energy Development, 2022)
Referred to by: Retraction notice to ‘Control of Bidirectional DC-DC Converter for Micro-Energy Grid’s DC Feeders' Power Flow Application' IJRED 11(2), 533-546International Journal of Renewable Energy Development, 12(6). https://doi.org/10.14710/ijred.2023.57139